Consolidation Behavior of Soft Soil Treated with PVDs and Vacuum-Surcharge Preloading - Le, Nghia Trong; Nguyen, Kien Trung; Nguyen, Minh Trung (Civil Engineering Journal, 2025)
Prefabricated vertical drain (PVD) combined with vacuum-surcharge preloading is a widely used ground improvement technique to accelerate the dissipation of excess pore water pressure and reduce the soil compressibility. However, difficulties in the numerical simulations of water dissipation and equivalent permeability of soil with PVDs in three-dimensional (3D) and two-dimensional (2D) settings cause substantial deviation of numerical results from observational data. Moreover, the optimum length of PVDs has not been well documented. Accordingly, this work analyzes a project in Dong Nai, Vietnam, where a 37-meter-thick soft soil was treated with PVDs and vacuum-surcharge preloading. In this work, the field observations and finite element method with consolidation theory were used to analyze the ground settlements, lateral displacements, and excess pore water pressure. The observed and simulated data shows that (i) the rate of settlements in the first 60 days of increasing preloading pressure is about 2.1 times faster than that in the next 110 days of constant preloading pressure, (ii) at 170 days, the ground-surface lateral displacement at the toe of the embankment is around 50 mm and reaches its maximum value of 150 mm at 1.55 m depth, and (iii) the dissipation of pore water pressure is closely correlated with the settlement rate. Moreover, back analysis indicates that a permeability conversion ratio from 1.872 to 4.538 should be applied to achieve the same degree of consolidation between 3D and 2D models. Lastly, the optimum length of PVDs in this project is 28 m, around 76% of the fully penetrated length into the soft layer.